Exploring the path to pathos “Lived experiences of parents of children with autism spectrum disorder”: An interpretative phenomenological analysis - Rajeev Ranjan; Meha Jain; Pankaj Kumar; Gabby Sethi; Jai Singh (Indian Journal of Psychiatry)
Background: Children with autism spectrum disorder (ASD) require lifetime support by the family, thus posing a great amount of stress among parents. Understanding lived experiences of parents who provide lifelong support will guide in planning effective treatment for children with ASD. In view of this, the study was aimed to depict and understand the lived experiences of parents of children with ASD and making sense of it. Methods: This interpretative phenomenological analysis research design was carried out on 15 parents of children with ASD coming to the tertiary care referral hospital of eastern zone of India. In-depth interviews were conducted to understand the lived experiences of parents. Results: The current study identified six themes: major symptom recognition; myths, beliefs, and stigma related to children with ASD; help seeking behavior; coping with challenging experiences; support system; uncertainties, insecurities, and gleam of hope. Conclusion: Lived experiences were found to be predominantly difficult for most of the parents of children with ASD, and inadequate services pose a major challenge to them. The findings highlight the need for involving the parents in the treatment programs as early as possible or extending appropriate support to the family.